Heartache Falls - March, Emily (March, Emily. Eternity Springs novel., 2011)
Married for more than twenty years, and with her children out of the nest, Ali Timberlake has come to Eternity Springs alone. She's looking for answers to heartbreaking questions and searching for something that's missing deep within herself. Taking a lease on the Bristlecone Café in pursuit of a lifelong dream, Ali feels revitalized as she becomes part of this charming mountain town. But a big piece of her is still back in Denver with her husband, Mac, a successful judge and a man who isn't going to let the woman he loves leave without a fight.